Assessment of groundwater quality and water table mapping of Bhaktapur Municipality - Ganesh, Razim; Koju, Rebika; Prajapati, Raja Ram (Journal of Science and Engineering, 2018)
Water is necessary for all life on earth. Every living creature on the Earth depends on water for their survival; however the supply of water on Earth is limited. Groundwater, the important source of water supply to many people around the world, is accessed through stone spouts, springs, dug wells and infiltration galleries in and around Kathmandu Valley since ancient time. The extraction of groundwater in Kathmandu Valley is increasing day by day due to increase in population, haphazard urbanization and unplanned industrialization. Drinking water quality and quantity is one of the major issues which need to be taken seriously, since clean water and sanitation are human rights and essential to life. The present study aims to prepare water table map and groundwater quality map from unconfined aquifer of Bhaktapur Municipality. Geographic Information System (GIS) based groundwater table mapping for 472 samples were used. Inverse Distance Weighted (IDW) method was used for 86 samples for spatial interpolation of chemical indices. Surface maps are prepared for water quality parameters (pH, turbidity, conductivity, TDS, total hardness, iron, ammonia, nitrate, chloride, alkalinity and E-coli) in the GIS Software by interpolation between the available data. Water table elevation map shows that groundwater levels are shallow at wells located close to agricultural field. From the water quality mapping of the Bhaktapur Municipality, it is seen that the most of the water quality parameters are within the maximum permissible limit set by WHO and NDWQS. It is noted that quality of ground water in the study area exceeds Nepal drinking water quality standards on the basis of measured values of chloride, ammonia and nitrate in majority of wells. High concentration of chloride, ammonia and nitrate were found in most of water samples from the central part and in around the periphery of the municipality boundary, which may be due to infiltration of agricultural runoff and leaching of sewage pollutants.